Database-driven charting using XSLT and SVG controlling finer details of data-driven scalable vector graphics. - Moharil, Avinash
Over the last few years, there have been significant developments in the XML world. Many enterprises have adopted XML for various purposes such as data transfer, reporting, client-tier presentation, server to server communication and so on.